Islamic Economy to Reduce Poverty in Indonesia According to the Al-Qur’an - M Rafi Mudzakky; Ryan Bianda; M Jahid Lilhaq (Penerbit Hellow Pustaka, 2024)
The poverty economy in Indonesia is a serious problem that requires attention and holistic solutions. This research aims to analyze efforts to overcome poverty by referring to economic principles in the Koran and Hadith. Through this approach, we can understand the Islamic view of social justice and economic distribution which can be the basis for more inclusive policies. This research identifies some of the main economic challenges facing Indonesia and analyzes how Islamic principles can be applied to overcome these problems. Efforts to empower communities through education, skills training and small business formation can be strategies that are in accordance with Islamic values. The results of the analysis show that the implementation of Islamic economic principles can make a significant contribution to reducing poverty levels in Indonesia. Therefore, policy recommendations include establishing regulations that support an equitable economic system, strengthening Islamic financial institutions, and increasing public awareness about socio-economic responsibility. This research contributes to our understanding of the potential for faith-based economic solutions to overcome poverty, and can become the basis for the development of more inclusive and sustainable policies in Indonesia.